Strategi Pembelajaran IPA di Pendidikan Non Formal pada Upaya Pemahaman Materi Peserta Didik: Studi di SKB Purwokerto - Aziz Kurniawan; Mohamad Mabarun (Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
Education plays a strategic role in advancing a nation. However, not all members of society have equal opportunities to access proper formal education, a condition that contributes to the high rate of school dropouts (APS). Therefore, the presence of non-formal education institutions, such as the Sanggar Kegiatan Belajar (SKB), serves as an alternative pathway for educational access and a platform for life-skill development. This study aims to analyze science (IPA) learning strategies in non-formal education as an effort to enhance learners’ understanding of the material. A qualitative approach with a case study design was employed in this research, conducted at SKB Purwokerto. Data were collected through observation, semi-structured interviews, and analysis of curriculum documents. The findings indicate that the implementation of education at SKB Purwokerto has been carried out systematically using a differentiation approach. In the learning process, mastery of basic science concepts, scientific skills, and connections to daily life are emphasized. Although there is a slight difference in the depth of material compared to formal education, non-formal education presents content in a simplified manner while maintaining the essential scientific aspects of IPA. In terms of learning resources, IPA tutors at SKB Purwokerto have maximized the use of government-provided modules, contextual simple experiments, and the seTARA LMS platform to support science learning. Therefore, this study concludes that SKB Purwokerto has implemented inclusive, adaptive, and relevant strategies for science learning that effectively support the development of meaningful understanding among learners.